Reliability forecasting for optimal planning of measures for maintenance of security systems of transport infrastructure facilities. (September 2020) - Tsarkova, E; Belyaev, A; Churakov, D; Andreeva, E
Abstract: The paper studies the methods for predicting the reliability of technical security equipment located at transport infrastructure facilities. The methods of determining the probability of the state of readiness of technical systems with various combinations of parameters of the maintenance system are considered. The automation capabilities are demonstrated in the study of the effectiveness of technical security equipment based on the analysis of their tactical and technical characteristics.